Seed‐mediated Growth of Au Nanoplates on the Functionalized Reduced Graphene Oxide Films for Surface‐enhanced Raman Scattering. (24th August 2017) - Kim, Young‐Kwan; Jang, Hongje; Kang, Kyungtae
Abstract : We developed a seed‐mediated growth strategy for the synthesis of Au nanoplate on the pyrene ethyleneglycol amine (PEA) functionalized reduced graphene oxide (PEA‐RGO) films. This process yielded 17.6% of Au nanoplates on the PEA‐RGO films, and the synthesized Au nanoplate/PEA‐RGO nanohybrid films showed high potential as a surface‐enhanced Raman scattering (SERS) platform. Abstract :